Gender, Politics and Islam: By Therese Saliba, Carolyn Allen, Judith A. Howard, eds. (Chicago and London: University of Chicago Press, 2002. 354 pages.) (American Journal of Islam and Society, 2004)
Though women’s studies and Islamic studies have not often met in scholarlydiscourse, Gender, Politics and Islam is evidence that they should. Thisbook is a testament to the breadth and quality of scholarship in Muslimwomen’s studies. All of its articles originally appeared in Signs: Journal ofWomen in Culture and Society, of which Therese Saliba, Carolyn Allen, andJudith A. Howard, previously served as editors and associate editors.Saliba’s competent introduction summarizes the articles and promptlydebunks simplistic understandings of Muslim women and their lives, and highlights their diverse and complex engagements with religion, politics,society, and culture. Not only does this introduction speak for and tonuanced understandings of Islam and Muslims, it also links feminist strugglestransnationally and explicitly positions itself against the exceptionalismof Muslim women.Although all nine chapters were previously published, this volumemerits separate publication for several reasons. First, it promotes goodscholarship on Muslim women. Second, it undoubtedly will reach a largeraudience as a collection than as individual articles. This audience includesnot only those outside academia, but also academics who might not normallyread specialized women’s studies journals – many in the field ofIslamic studies, traditionally defined, for example. Moreover, the bookcould be used effectively in teaching Islamic studies and women’s studies;indeed, some of its articles are already being used this way. Though thearticles were not written for a general audience, many could easily appealto the interested nonspecialist.Finally, these serious, scholarly essays complement each other and representa breadth of disciplinary approaches (e.g., literary studies, sociology,history, anthropology, and political science), geographical regions (e.g.,Iran, Pakistan, Palestine, Lebanon, Yemen, Bangladesh, and Canada), andissues (e.g., legal rights, religious rituals, political empowerment, receptionpolitics, and Islamic feminism, among many others). Despite this breadth,each essay speaks extremely well to at least several others and highlightsMuslim women’s strategies and practices of crafting spaces for action andengagement in politics and society.Valentine Moghadem’s “Islamic Feminism and its Discontents:Towards a Resolution of the Debate” provides an overview of Iranianwomen’s many contrasting positions in relation to their rights in theIslamic Republic. She also draws useful comparisons between U.S. liberalfeminists and Iranian Islamic feminists, thereby providing an analysisof current trends, issues, and debates. “The Politics of Feminism inIslam,” by Anouar Majid, continues this inquiry into women crafting afeminist theory and practice that engages Islam. Like Moghadem, he seesa positive side to Iran’s Islamic feminist movement, as it resists “theeffects of global capitalism and contributes to a rich egalitarian polycentricworld” (p. 87) ...